Analisis Proses Penganan Klaim Produk Asuransi Umum Di PT Asuransi Umum Bumiputera 1967 Cabang Medan - Novita Sari; Rahmi Syahriza (Public Service and Governance Journal, 2025)
This article discusses the claims handling process at PT Asuransi General Bumiputera 1967 Medan branch. The aim of this research was to analyze the process of handling claims for general insurance products at PT Asuransi General Bumiputera 1967 Medan Branch. The research method used is a descriptive approach with qualitative methods. Data collected through in-depth interviews with staff employees and field practitioners was carried out to gain a better understanding of the claims handling process, and direct observation allowed researchers to see the procedures carried out. The research results show that the process of handling general insurance product claims at PT Asuransi General Bumiputera 1967 Medan Branch includes several stages, namely claim acceptance, document verification, claim investigation, claim assessment, and claim payment. This process involves various parties, including claims officers, claims experts and customers. In conclusion, the existing systems and procedures at PT Asuransi General Bumiputera 1967 Medan branch have provided satisfactory results in the process of handling general insurance claims, but need to continue to be improved in accordance with technological developments and customer needs.